Enhancing biomass, hydrocarbon and biodiesel properties of green microalga Botryococcus braunii KMITL through gamma and UV radiation exposure - Buppha Jongput; Pattanasak Chiwpreecha; Suneerat Ruangsomboon; Pajongjit Tongsri (Scientific Reports)
Abstract This study investigated the effects of gamma (137Cs, 0–250 Gy) and UV (UV-C, 0–12 h) radiation on growth and biodiesel properties of Botryococcus braunii KMITL. For gamma radiation, maximum biomass (1.37 ± 0.02 g L−1) was achieved with 50 Gy, while a dose of 200 Gy resulted in the highest hydrocarbon content (51.84 ± 0.20%) and yield (0.66 ± 0.01 g L−1). For UV radiation, a 9 h exposure produced the highest biomass (2.45 ± 0.05 g L−1), hydrocarbon content (55.01 ± 1.22%), and yield (1.35 ± 0.04 g L−1). Algae exposed to gamma radiation within the range of 0–150 Gy exhibited C16:0 as the dominant fatty acid methyl ester (FAME), similar to those exposed to UV radiation, while algae exposed to 200–250 Gy displayed C18:1n9t as the dominant FAME. High levels of gamma and UV radiation were observed to lengthen fatty acid chains and increase unsaturated fatty acids. The cetane values of biodiesel from algae exposed to gamma and UV radiation ranged from 64.55 ± 0.14–66.47 ± 0.20 and 59.43 ± 0.04–65.27 ± 0.22, respectively, all meeting standard criteria. Both gamma and UV radiation also improved the saponification value and cold flow properties of the biodiesel. These findings suggest that controlled levels of gamma and UV radiation effectively enhance hydrocarbon yields with significant implications for biofuel production.